The amounts of fluorides (alkali-soluble as well as insoluble) gained of and in enamel of third molars from a high fluoride area - Van Zyl, Jacobus Francois (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Dental Sciences)) -- University of Stellenbosch, 1992.